Integrated stakeholder-centered tourism crisis - Pennington-Gray, Lori; Basurto-Cedeno, Estefania (Frontiers in Sustainable Tourism, 2023)
The present work demonstrates how non-traditional tourism stakeholders' inclusion in planning and decision-making improves connectivity and helps to achieve resilience in rural tourist destinations. The geographical and temporal context for the study is the sector of El Balsamo in Manabi-Ecuador, during the COVID-19 pandemic.This study makes evident how the creation of networks and partnerships leveraged on effective communication and the prioritization of common objectives allows the permanence of these networks even after the crisis has been overcome. The methodology applied is a case study with data collection through interviews and applying the MERITS method to identify recurring themes when various stakeholders' opinions are included. The results of this study show the importance of inclusion and effective communication in building trust and long-term alliances in destination recovery processes.